The Effect of Discovery Learning to Teach Students’ Reading Comprehension - Rahayu Meliasari; Adek Sunita; Sahrawi Sahrawi; Maliqul Hafis (IKIP PGRI Pontianak, 2023)
This research evaluates the efficacy of the discovery learning method in enhancing reading comprehension for tenth-grade students at SMK Mandiri Pontianak in the academic year 2023/2024. Employing a pre-experimental design, the sample for this study was chosen from the TKJ A class using cluster random sampling. The data collection process included both pre-tests and post-tests. Findings indicated a significant improvement in students' reading comprehension through the implementation of the discovery learning method, evident in the transition from a pre-test score of 61 (averaged) to a post-test score of 83 (excellent Statistical analysis through the t-test validated a noteworthy distinction (a < 0.05), affirming the dismissal of the null hypothesis (H0). This signifies a statistically significant enhancement in reading comprehension following the implementation of the discovery learning method.